2020
DOI: 10.3390/antibiotics9060303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Diagnosis-Centered Antibiotic Stewardship on Incident Clostridioides difficile Infections in Older Inpatients: An Observational Study

Abstract: In 2015, a major increase in incident hospital-onset Clostridioides difficile infections (HO-CDI) in a geriatric university hospital led to the implementation of a diagnosis-centered antibiotic stewardship program (ASP). We aimed to evaluate the impact of the ASP on antibiotic consumption and on HO-CDI incidence. The intervention was the arrival of a full-time infectiologist in the acute geriatric unit in May 2015, followed by the implementation of new diagnostic procedures for infections associated with an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For hospitalized patients, testing is recommended only in cases with diarrhea, defined as 3 consecutive unformed stools. Incidence of C. difficile diarrhea is higher in elderly patients (1,(18)(19)(20). The same patient may present another episode of C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hospitalized patients, testing is recommended only in cases with diarrhea, defined as 3 consecutive unformed stools. Incidence of C. difficile diarrhea is higher in elderly patients (1,(18)(19)(20). The same patient may present another episode of C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription is higher in the ambulatory setting. An increase in antibiotic use can also lead to an increase of asymptomatic hosts which produce more spore contamination (1)(2)(3)(4)(5)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Both oral metronidazole and vancomycin appear to have the same efficacy for mild and moderate forms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, de Miguel-Diez et al [ 27 ] and López-de-Andrés et al [ 7 ] reported an association between comorbidities and decreased hospital mortality risk, included type 2 diabetes mellitus for the total population (OR: 0.97, 95% CI: 0.91–1.01), for men (OR 0.95, 95% CI: 0.90–1.02), and women (OR 0.99, 95% CI: 0.93–1.04); and COPD among women admitted to the hospital with an episode of UTI (OR 0.99, 95% CI: 0.93–1.04). This association may, in part, be explained by: 1, greater awareness of UTIs and overall infection risk among older patients [ 29 , 39 ], which may be a consequence of the higher degree of vigilance among patients, family members, and healthcare providers to seek and report typical symptoms of UTI (dysuria, urinary frequency, fever, back/flank pain) and nonspecific symptoms (acute confusion, behavioral disturbances, falls); 2, more accessible outpatient health-care [ 29 ]; 3, early use of diagnostic techniques [ 39 ]; 4, higher hospitalization rate with less severe UTIs [ 9 ]; 5, better antibiotics, better hospital protocols for the treatment of infections [ 39 ]. Consequently, these would facilitate early detection, a greater likelihood of UTI diagnosis, and timely treatment.…”
Section: Discussionmentioning
confidence: 99%